Pin-on-disc characterization of 2xxx and 6xxx aluminium alloys aged by precipitation age hardening - Meyveci, Ahmet; Karacan, Ismail; Caligulu, Ugur; Durmus, Huelya (Elsevier Science Sa, 2010)
In this study, wear behaviors of aged aluminium AA 2024 and AA 6063 alloys were investigated. AA 2024 and AA 6063 aluminium alloys were solution treated at two different temperatures of 490 and 520 degrees C. Then all samples were cooled to room temperature. After this process, the samples were aged at three different temperatures (140 degrees C, 180 degrees C and 220 degrees C) for five different periods of time (2, 4, 6, 8, 10). The microstructures of the aged samples were examined by optical microscope, SEM-EDS and X-ray analysis. The hardness values of the aged samples were measured by microhardness tests. Wear tests were carried out on the pin-on-disc model wear test apparatus under sliding velocity at 2 m s(-1) speed, 400, 800, 1200 and 1600 m sliding distances for 10, 20 and 30 N variable loads. The mass-loss values of the aged samples were tested by wear tests. As a result of this study, the hardness of the second phase precipitated samples was found to be higher than that of the as-cast samples and it increased with increasing the solution temperature and aging periods. The study also revealed that the wear rate and friction coefficient can be decreased with increasing the solution temperatures and aging periods. Crown Copyright (c) 2009 Published by Elsevier B.V. All rights reserved.
Keywords: SEM; Metals; Alloys; Metallography